PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP MOTIVASI BELAJAR SISWA DI SEKOLAH DASAR - Aulia Putri; Mohamad Muspawi; Rohmatika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Project-Based Learning (PjBL) model on students’ learning motivation through a literature study method. Data were obtained from various national and international journals discussing the implementation of PjBL and its impact on learning motivation. The findings indicate that PjBL is able to increase students’ motivation because project-based activities encourage active engagement, collaboration, creativity, and responsibility in completing tasks. In addition, PjBL provides meaningful and contextual learning experiences, making students more enthusiastic, focused, and motivated during the learning process. Thus, PjBL can be recommended as an effective learning model to enhance students’ learning motivation.